3D Reconstruction for Simultaneous Localisation and Mapping System (SLAM) in Robotics using Webcam Images - Sia , Benny Wan Fung (Universiti Teknologi Petronas, 2010)
The purpose of this research is to study on 3D reconstruction using webcam images in indoor environment. The research is focused on computer vision and image processing for robotics. It aims to design a simple but efficient 3D reconstruction technique which could be used as part of the Simultaneous Localization and Mapping (SLAM) system in robotics and autonomous vehicles.